2015
DOI: 10.2500/ajra.2015.29.4170
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phosphorylation of STAT5b, but not STAT5a, in Nasal Polyps

Abstract: Analysis of these data indicates distinct expression and activation of STAT5a and STAT5b in nasal polyps, particularly the activation of STAT5b. It is possible that STAT5b may contribute to the development of nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The receptors for these cytokines activate JAKs by phosphorylation of STAT1, STAT3, STAT4, STAT5, and STAT6, suggesting that the JAK/STAT pathway is involved in the pathogenesis of chronic lower respiratory tract inflammatory diseases [7,9,10]. In a study on JAK/STAT signaling in CRS, Linke et al revealed distinct expression and activation of STAT5b in nasal polyps, suggesting that STAT5b may contribute to the development of nasal polyps [11]. Moreover, dupilumab blocks both IL-4 and IL-13 signaling in treatment for patients with moderate to severe CRSwNP, thereby modulating downstream STAT6 or STAT3 phosphorylation via inactivation of JAK1 or JAK2; subsequently inflammation and tissue remodeling is able to be controlled and regulated [12].…”
Section: Introductionmentioning
confidence: 99%
“…The receptors for these cytokines activate JAKs by phosphorylation of STAT1, STAT3, STAT4, STAT5, and STAT6, suggesting that the JAK/STAT pathway is involved in the pathogenesis of chronic lower respiratory tract inflammatory diseases [7,9,10]. In a study on JAK/STAT signaling in CRS, Linke et al revealed distinct expression and activation of STAT5b in nasal polyps, suggesting that STAT5b may contribute to the development of nasal polyps [11]. Moreover, dupilumab blocks both IL-4 and IL-13 signaling in treatment for patients with moderate to severe CRSwNP, thereby modulating downstream STAT6 or STAT3 phosphorylation via inactivation of JAK1 or JAK2; subsequently inflammation and tissue remodeling is able to be controlled and regulated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Lam et al 3 used sinus mucosal samples to demonstrate increased IL-25 and IL-33 expression, but not TSLP expression, in patients with chronic rhinosinusitis, nasal polyps, and >10 eosinophils/high power field, in a comparison study with normal control tissue. Linke et al, 4 in another study using human samples, this time nasal polyps and inferior turbinate tissue, found that STAT5b, but not STAT5a, is activated compared to controls in patients with chronic rhinosinusitis and nasal polyps. Finally, Esmaeilzadeh et al 5 identified genetic variabilities of major histocompatibility complex class II for patients with aspirin exacerbated respiratory disease, suggesting a role for T cell activation in the pathophysiology of this disease process.…”
mentioning
confidence: 98%